(3EjVGM GdGQJjGH aj eYQaI eG jTJHg hjJUMa ef GdCSeGA hGdCfSGH hGdCdaGX hGdCdbGHs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s ((3eMeO Hf SdjeGf Hf YhV GdHcQi s)
(3ChdgG (B:s
(3bGd eDdag GdTjN GdEeGe GdTgjQ HGHf CHj GdMSf GdfMhi hbOSFdJ Cf CdMb HBNQ gPG GdcJGH aUdG eNJUQG ai VHW eG jTcd Ydi ef GdCSeGA hGdCdaGX s
(3BNQgG (B:s
(3aEfj YdbJ Pdc ai HYV jhejf ef TgQ QeVGf GdeYXe ef SfI NeS hNeSjf hSHYeGFIq s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B57s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B153s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs